Seirra Swanson: capstone - Swanson, Seirra, artist (Colorado State University. Libraries, 2021)
The artist's statement: I often find myself seeking out nature for clarity and artistic inspirations. My body of work intertwines nature and technology, creating a dichotomy between the wonder of the natural world and the industrial uses of technology. Recently I often find myself experimenting with the different visuals I can create only occasionally turning back to the natural environment. My works mainly focus on 3D modeling, animation, video, and the occasional code used to distort images. I often use the organic shape and movement of the environment as a starting point. The icons resembling nature will later become distorted, as this nature is manmade much like the technology destroying it. Through processes like drawing, animating and 3D modeling I can deconstruct and reconstruct the idea of the natural environment in a digital form.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art